2016
DOI: 10.1177/1534735416679516
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Lifestyle Randomized Clinical Trial: Design and Initial Patient Experience

Abstract: Background Although epidemiological research demonstrates that there is an association between lifestyle factors and risk of breast cancer recurrence, progression of disease, and mortality, no comprehensive lifestyle change clinical trials have been conducted to determine if changing multiple risk factors leads to changes in biobehavioral processes and clinical outcomes in women with breast cancer. This article describes the design, feasibility, adherence to the intervention and data collection, and patient ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 92 publications
0
8
0
Order By: Relevance
“… 57 The lifestyle interventions at the Block Center may have contributed to the good condition of the patients, but the study was not intended or designed to make conclusions about this possibility. The analysis cannot determine whether participants improved their CO soon after beginning the chronomodulated chemotherapy and systematic supportive integrative treatment protocols, 58 60 or whether they simply maintained preexisting good CO throughout chemotherapy regimens. 31 …”
Section: Discussionmentioning
confidence: 99%
“… 57 The lifestyle interventions at the Block Center may have contributed to the good condition of the patients, but the study was not intended or designed to make conclusions about this possibility. The analysis cannot determine whether participants improved their CO soon after beginning the chronomodulated chemotherapy and systematic supportive integrative treatment protocols, 58 60 or whether they simply maintained preexisting good CO throughout chemotherapy regimens. 31 …”
Section: Discussionmentioning
confidence: 99%
“…Such multitargeted interventions have been described in the literature, [15][16][17][18] and one experimental study of such a system published in this journal even included remote delivery of lifestyle counseling using Facetime. 17 While in-person counseling has significant advantages, the safety and potential economy of telehealth consultations with integrative physicians, dietitians, and specialists in psychosocial oncology may allow for very relevant interventions, particularly for patients in treatment. Referrals to in-person therapies can be made for lower-risk patients, perhaps at locations outside the treating hospital if necessary.…”
Section: Telehealth: a Focus On Biologymentioning
confidence: 99%
“…The majority of structured programs target either dietary or physical activity changes (Demark-Wahnefried et al, 2012 ). However, in recent years there has been an increase in more integrative lifestyle interventions that target different mind-body factors with potential impacts on both weight-loss and quality of life such as motivation, self-efficacy, yoga, sleep, and meditation (Arun et al, 2017 ; Larkey et al, 2014 ; Lyman et al, 2018 ; Reeves et al, 2014 ). One comprehensive review on the effectiveness of such interventions identified several characteristics of more successful lifestyle trials (O’Connell et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%